The Relationship Between the Level of Compliance with Antiretroviral Treatment and the Quality of Life Of HIV/AIDS Patients at Bekasi District Hospital - Ahfad Saeroji; Yogi Giantara (Sean Institute, 2026)
The increasing number of HIV/AIDS cases in Indonesia requires optimal management through Antiretroviral (ARV) therapy to improve the quality of life of patients. Adherence to ARV medication is a key factor in the success of therapy and achieving optimal quality of life for HIV/AIDS patients (Kemenkes RI, 2024). This study aims to analyze the relationship between the level of ARV treatment adherence and the quality of life of HIV/AIDS patients at RSUD Kabupaten Bekasi. The research method used is observational analytic with a cross-sectional approach. The study sample consisted of 133 people with HIV/AIDS undergoing ARV therapy, selected using the total sampling technique (Sugiyono, 2020). The results showed a significant relationship between the level of ARV treatment adherence and the quality of life of HIV/AIDS patients (p = 0.001 < 0.05). Based on this research can be concluded that the Correlation Coefficient value of 0.558 indicates a moderate relationship, where high adherence positively influences the quality of life, especially in physical health and patient independence. Frequency distribution showed that 56.7% of respondents had low adherence, 40% moderate, and 3.3% high, with 43.4% having poor quality of life, 46.7% fair, and 10% good.Tthese findings indicate that adherence to ARV treatment plays an important role in improving the quality of life of HIV/AIDS patients. Therefore, continuous education and support are needed to enhance patient adherence.